2020
DOI: 10.1016/j.jsps.2019.11.011
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory effects of isolated constituents from Plantago major subsp. major L. on collagenase, elastase and hyaluronidase enzymes: Potential wound healer

Abstract: Plantago major L. which is a medicinal plant with important biological activities, commonly used as traditional medicine. Potential inhibitory activities of the aqueous extract and three isolated constituents calceorioside B (1), homoplantaginin (hispidulin-7-O-glucoside) (2) and plantamajoside (3) from the aerial parts of Plantago major subsp. major L. (Plantaginaceae) have been tested against hyaluronidase, collagenase, and elastase, which play critical roles in wound pathogenesis. Even though, the extract (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 45 publications
0
20
0
1
Order By: Relevance
“…Estimation was based on IC 50 values as follows: IC 50 ≤ 20 μg/mL, highly active; IC 50 = 21–200 μg/mL, moderately active; IC5 0 = 201–500 μg/mL, weakly active; and IC 50 > 501 μg/mL, inactive, which is in a good accordance with the American National Cancer Institute protocol ( Al-Yousef et al, 2020 )The results showed that PAE possesses a moderate cytotoxic activity with IC 50 = 56.9 ± 3.1 and 95.8 ± 3.8 µg/mL for HepG-2 and MCF-7cell lines compared to cisplatin with IC 50 = 3.67 ± 0.22 and 5.71 ± 0.57 μg/ml, respectively. PAE activity may be attributed to the presence of vitexin ( He et al, 2016 ), homoplantaginin ( Genc et al, 2020 ), orientin ( Lam et al, 2016 ) and butin (3′,4′,7-trihydroxyflavanone) ( Zhang et al, 2011 ). During this work, vitexin, orientin, homoplantaginin, and butin were detected in LC-MS analysis of ethyl acetate fraction as major compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Estimation was based on IC 50 values as follows: IC 50 ≤ 20 μg/mL, highly active; IC 50 = 21–200 μg/mL, moderately active; IC5 0 = 201–500 μg/mL, weakly active; and IC 50 > 501 μg/mL, inactive, which is in a good accordance with the American National Cancer Institute protocol ( Al-Yousef et al, 2020 )The results showed that PAE possesses a moderate cytotoxic activity with IC 50 = 56.9 ± 3.1 and 95.8 ± 3.8 µg/mL for HepG-2 and MCF-7cell lines compared to cisplatin with IC 50 = 3.67 ± 0.22 and 5.71 ± 0.57 μg/ml, respectively. PAE activity may be attributed to the presence of vitexin ( He et al, 2016 ), homoplantaginin ( Genc et al, 2020 ), orientin ( Lam et al, 2016 ) and butin (3′,4′,7-trihydroxyflavanone) ( Zhang et al, 2011 ). During this work, vitexin, orientin, homoplantaginin, and butin were detected in LC-MS analysis of ethyl acetate fraction as major compounds.…”
Section: Resultsmentioning
confidence: 99%
“…as it has an antibacterial property and many important biological activities which includes iridoid glucosides, phenylethanoid glycosides, flavonoids, terpenoids, phenolic acids and polysaccharides. 26 Many research and experiments have also been performed on the utilization of this plant and its other species for its antipeptic activity. 27…”
Section: Resultsmentioning
confidence: 99%
“…It is a chief protein present in the extracellular matrix (ECM) of joints. For elastase inhibition assay, N-Suc-(Ala) 3-nitroanilide was used as the substrate 8,9 . The release of γ-nitro aniline was measured spectrophotometrically at 410 nm in a 96-well reader 10,11 .…”
Section: Preparation Of Plant Extract and Preliminary Phytochemical Amentioning
confidence: 99%